Mana ile hadis rivayeti - Atan, Abdullah Hikmet (My University, 1999)
NARRATION OF HADİTH BY MEANING (MA'NA) Hadiths attract a wide range of research from the point of their contents, their narration and narrators. The main goal of these researchs is to provide Islamic societies with proper knowledge about Sunnah by way of differentiating between sahih Sunnah and ghayr sahih ones. One of the most important subjects about narrators' disposals (tasarruf) on hadith texts is narration of hadith by meaning. The importance of this subject stems from the fact that narrators' disposals are directly related to the meaning of hadith. Being different in nature from Qur'an which is narrated without any change of word, hadiths were generally narrated with changes although some of them are trivial Historically, narration of hadith by meaning took place in the early period of hadith, that is to say, from the beginning to the end of tadwin. As every differentiation in the text can not be counted as narration by meaning, every kind of disposals of narrator on the text is not narration by meaning. The conditions of narration by meaning which are observed by narrators limit the way of narration so that they prevent arbitrariness. This is a result of religious and scientific behaviour. Narration of hadith by meaning affected different fields of Islamic sciences, one of them is Arabic grammar. The two other most important fields are aqaid and fiqh. Narration by meaning doesn't pose a prevention to the protection of the message of the Prophet (s.a.).
Keywords: İSLAM DİNİ-HADİS